History of anaesthetics - Mason, Kirk P. (My University, 1904)
Introduction: The use of anaesthetics (anesthetic) has been known for hundreds of years. The art of catalepsis, a sort of mesmerism, was one of the first methods of allaying pain that was put into practice. Herodotus, a Greek historian B. 0. 484-420, Pliny, a Roman naturalist 23-79, and Dioskorides, a Greek medical writer who flourished in the second century, mention in some of their manuscripts drugs that were used for the purpose of deadening pain. Mandragora was used by Italian physicians for this purpose. There is a Chinese physician who is credited with having used Cannabis, hemp, for the purpose of obviating the pains of surgical operations, by inhalation. It has been claimed that physicians of the Middle Ages were very skillful in the producing of insensibility by artificial means, and that many of the astonishing exhibitions of unconsciousness to pain were the effect of drugs and vapors. Sir Humphrey Davy, 1778-1829, one of the leading English chemists, appears to have been the first to comprehend the practicability of using anaesthesia (anesthesia) for surgical purposes. He discovered that nitro-genic protoxide would, with a reasonable degree of safety, remove the sense of pain and set the mind free from its bodily duties. Michael Faraday, a pupil of Davy's, secured similar results from inhaling sulphuric ether, but it was not until the latter part of the century that this was put to any practical use. It was then that Crawford W. Long of Georgia, Horace Wells of Hartford, and William T. G. Morton of Boston ventured to make some practical demonstrations with it. The latter two, who were dentists, used it in their practice, Wells using nitrous oxide, and Morton, sulphuric ether. Morton's success was so complete that he induced a surgeon to use it in the hospital. After many trials and legal conflicts the credit for the discovery was conceded to Morton. At first his discovery was not accepted very generally in the United States, but received a very speedy appreciation abroad. In the preceding lines I have tried to give a brief history of the use of anaesthetics (anesthetics) leading up to the discovery of the use of ether by Morton.
Citation: Mason, Kirk P. History of anaesthetics. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Anaesthetics; Anesthetics; Ether; Pain relief; Theses